The trajectory of repairs in the defibrillator sequence during emergency cardiac arrest calls - Balancing progressivity and intersubjectivity. (17th February 2022) - Perera, Nirukshi; Riou, Marine; Ball, Stephen; Birnie, Tanya; Morgan, Alani; Whiteside, Austin; Bray, Janet; Bailey, Paul; Finn, Judith
Abstract : Due to the urgent, time-sensitive nature of interactions in emergency ambulance phone calls, dealing with repairs (communication trouble) can be challenging. We investigate a critical medical emergency known as out-of-hospital cardiac arrest (OHCA) and focus on how ambulance call-takers handle repairs during an interactive sequence concerning the retrieval of automatic external defibrillators (AED). Clear communication about AEDs is vital, because the device can deliver a life-saving shock to an OHCA patient's heart. We examined repair initiations, and their subsequent trajectories, during the defibrillator sequences in 58 OHCA emergency calls. We found evidence of competing influences in resolving such repairs: (1) providing a repair solution (including ensuring caller comprehension of what a defibrillator is) to achieve intersubjectivity that could resolve the question of defibrillator availability; or (2) progressing the call as swiftly as possible to an immediately applicable life-saving intervention such as cardiopulmonary resuscitation. The findings suggest that in certain institutional contexts, such as emergency medical service dispatch, the resolution of repairs in communication can take varying trajectories in order to achieve the most feasible goal in immediate time. We suggest that emergency medical services consider these trajectories in helping ambulance call-takers anticipate repairs in OHCA calls.